ANALYSIS OF PROFESSIONALITY OF BHAYANGKARA PERSONNEL OPERATIONAL AT THE STATE SECURITY DIRECTORATE OF THE SECURITY INTELLIGENCE AGENCY OF INDONESIAN NATIONAL POLICE - Resdiana, Artanti; Ridwan Radjab, Ridwan; Widjayanti, Arifiani (Jurnal Apresiasi Ekonomi, 2024)
The professionalism of State Security Directorate personnel is crucial for achieving superior, sharp, and reliable security intelligence. However, there is ambiguity in the placement of operational supervisory roles within the Directorate. The researcher identifies performance, competence, Loyalty, and accountability as key factors influencing the professionalism of the Indonesian National Police Security Intelligence's operational supervisory personnel (BOP). The research's primary objective is to analyze the issues surrounding the mismatch between BOP placements and operational directorate needs. It also aims to devise effective strategies to enhance BOP personnel professionalism. The research employs qualitative methods, including literature review, observations at the State Security Directorate, and interviews. The findings reveal three main issues. First, suboptimal professionalism is attributed to inadequate technical, managerial, and sociocultural competencies affecting performance. Second, the soft tools, such as career policies and functional positions in the Security Intelligence operational directorate, need optimization. Finally, increased performance, competence, Loyalty, and accountability are vital drivers for enhancing the professionalism of operational supervisory personnel within the State Security Directorate of the Indonesian National Police Security Intelligence Agency. Keywords: performance, competence, Loyalty, accountability and professionalism